Autocrine growth and tumorigenicity of interleukin 2-dependent helper T cells transfected with IL-2 gene (The Rockefeller University Press, 1989)
We introduced a mouse IL-2 cDNA expression vector into an IL-2- dependent mouse helper T cell line HT-2. Transfected cells secreted substantial amounts of IL-2, to which they themselves responded by proliferating without further requirement for exogenous IL-2. The proliferation was a direct function of the cell density and was inhibitable by antibodies against IL-2 or IL-2-R, indicating the autocrine nature of the proliferation. Those producing higher amounts of IL-2 were found to be tumorigenic when inoculated into nude mice. The latency period of tumor development correlated inversely with the level of IL-2 secreted. Tumor cells proliferated in vitro in an IL-2 autocrine fashion indistinguishable from that of the inoculated cells. We thus provide evidence that the aberrant activation of the IL-2 autocrine circuit can lead T cells to malignant transformation.